Does Artificial Intelligence devalue "Human" in Human Resources Management? - Muryani, Endang; Hariyanto, Dwi Widi; Supartini, Supartini; Mranani, Novelia Asita; Basroni, Fajar (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The rapid evolution of information technology besides helping humans in their work also has the potential to get rid of humans. From these two conditions, this study was made with the aim of answering how HRD will view employee performance which is dominantly resolved by AI, the trade off dilemma of AI and human workers and how to achieve an equilibrium between human and AI performance. This study used a literature review technique, but the results found that AI is still used in the majority of the recruitment and selection process, not in the function of human development. One question that cannot be answered in this study because the answer must be a joint agreement between academics, practitioners and company management.